Manfaat Renang Terhadap Pengurangan Tingkat Stres pada Mahasiswa PJKR UMMUBA - Bani Pilitan, Raja; Prahagia, Yelvia; Nuraini, Fadila (Jurnal Muara Olahraga, 2025)
Students in the Physical Education, Health, and Recreation (PJKR) Study Program at the State Islamic University of Muhammadiyah Muara Bungo (UMMUBA), as a group with a background in physical activity, are an important subject for study in the context of stress management through exercise, particularly swimming. Swimming is considered to provide relaxation and psychological well-being, making it interesting to examine more deeply the students' direct experiences. This study used a qualitative approach with phenomenological methods. The results clearly demonstrate that swimming is not merely a physical activity but also an effective comprehensive intervention in managing and reducing stress levels among students. Its benefits are diverse, including physical relaxation, increased positive feelings, the creation of personal space, and an overall improved quality of life. These findings provide a deeper understanding of how students perceive and utilize swimming as a vital strategy for coping with both academic and personal stress. This study recommends swimming as a worthy option for student wellness programs.